2023
DOI: 10.3389/fonc.2023.1230698
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preoperative CT- and MRI-based multiparametric radiomics in the prediction of lymph node metastasis in rectal cancer

Yue Niu,
Xiaoping Yu,
Lu Wen
et al.

Abstract: ObjectiveTo compare computed tomography (CT)- and magnetic resonance imaging (MRI)-based multiparametric radiomics models and validate a multi-modality, multiparametric clinical-radiomics nomogram for individual preoperative prediction of lymph node metastasis (LNM) in rectal cancer (RC) patients.Methods234 rectal adenocarcinoma patients from our retrospective study cohort were randomly selected as the training (n = 164) and testing (n = 70) cohorts. The radiomics features of the primary tumor were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…In our study, we found signi cant associations between preoperative CA19-9 levels, mrN, and distant metastasis in tumors with lymph node metastasis (p < 0.05), which is consistent with previous research conclusions (31,32).To further verify the clinical application value of radiomics models and explore ways to improve their diagnostic e ciency and stability, we combined three clinical risk factors with SR- This study still has limitations. First, as a retrospective study, in order to make the pathological results more accurate and reliable, this study only collected patients who underwent surgery.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found signi cant associations between preoperative CA19-9 levels, mrN, and distant metastasis in tumors with lymph node metastasis (p < 0.05), which is consistent with previous research conclusions (31,32).To further verify the clinical application value of radiomics models and explore ways to improve their diagnostic e ciency and stability, we combined three clinical risk factors with SR- This study still has limitations. First, as a retrospective study, in order to make the pathological results more accurate and reliable, this study only collected patients who underwent surgery.…”
Section: Discussionsupporting
confidence: 89%